Ab initio investigation of the ground and excited states of TcO+ and RhO+. (April 2022) - Ariyarathna, Isuru R.; Miliordos, Evangelos
Highlights: Multi-reference configuration interaction applied to ground and more than ten excited states of TcO + and RhO + . Bonding schemes and spectroscopic data are compared with neighboring metal oxides. TcO + has a pure triple bond and resembles RuO 2+ . Six electronic states lie within 3, 000 cm −1 from the ground state of TcO +, whereas the ground state of RhO + is well separated. Abstract: High-level quantum calculations are utilized to analyze nineteen and thirteen lowest energy electronic states of TcO + and RhO + . Their potential energy curves, equilibrium bond lengths, electronic excitation energies, harmonic vibrational frequencies, and anharmonicities are reported using quadruple-ζ and quintuple-ζ quality correlation consistent basis sets. The core electron correlation effects and equilibrium chemical bonding patterns of several low-energy electronic states are also considered. The ground state of TcO + (1 1 Ʃ + ) (1σ 2 1π 4 1δ 4 ) is triple bonded in nature, results adiabatically from the high energy Tc + ( 3 P) + O( 3 P) fragments, and relates to the first excited state of TcO ( 2 Σ + ) (1σ 2 2σ 1 1π 4 1δ 4 ). The chemical bonding of TcO + (1 1 Ʃ + ) is identical to its isoelectronic RuO 2+ (X 1 Ʃ + ) ground state. The ground state of RhO + ( 3 Σ − ) features a 1σ 2 1π 4 1δ 4 2π 2 electronic configuration. Moving from TcO + to RhO + the binding energy decreases by ∼15−20 kcal/mol, the metal-oxygen bond shortens by 0.07 Å, and the harmonic stretching frequency decreases by ∼170 cm −1 . Bonding patterns and spectroscopic constants are compared for the neighboring species of RhO + and TcO + .